Hydrolysis of αs2-casein in solution by chymosin, plasmin, trypsin and Lactobacillus-proteinases - Anne Pihlanto-Leppälä; Eero Pahkala; Minna Kahala; Veijo Antila (Agricultural and Food Science, 1993)
The aim of this study was to examine the enzymic hydrolysis of αs2-casein by isolating and identifying the released peptides. The enzymes applied in the study were chymosin, plasmin and trypsin as well as cell free extracts from three strains of Lactobacillus helveticus and nine strains of L. casei. The findings showed that chymosin had weak proteolytic activity on αs2-casein. Plasmin, on the other hand, released numerous peptides under the used conditions. The majority of the identified fragments were released from the C terminal end of the substrate. Plasmin hydrolysed mainly Lys-X bonds. The third enzyme, trypsin, hydrolysed several bonds of αs2-casein. Peptides were released from almost all regions of the protein. Trypsin acted on the carboxyl sides of arginyl and lysyl residues. Cell free extract of lactobacilli had little activity on αs2-casein.